PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAKE AND GIVE PADA MATERI MINYAK BUMI DI KELAS X MAN SABANG - Perwiraga Hartami; Ramli Abdullah; Yeni Safitri (UIN AR-RANIRY, 2014)
Based on observations made in class X2 MAN Sabang shows that learning still many students find it difficult to study chemistry, because the presentation material provided by the teacher is not maximized, so that the learning outcomes of students do not reach the target set in the KKM (70). This can be seen from the value of the task and the replay of students who gained an average of 66.2. One alternative to solve this problem is to use a cooperative learning that is easy to understand and fun through cooperative learning methods Take and Give. The purpose of this study was to: (1) determine student learning outcomes in the material of petroleum by using cooperative learning model type Take and Give, (2) Knowing student activity during learning using cooperative learning model type Take And Give, (3) Knowing the response students to the implementation of cooperative learning model of Take and Give. The design of this study is to use pre-experimental research design. The population in this study were all students of class X which consists of three local student learning outcomes is still relatively very low, then the sample in this study were all students of class X-2, which consists of 20 students. Data collection techniques using observation and administration of the test in the form of multiple choice. Observation data analyzed by using percentage, while the test results were analyzed by percentage formula. The research proves that: (1) student learning outcomes in the petroleum material once taught using cooperative learning model take and give to the percentage of the final test is 73%. (2) the percentage of students learning activity reached 76.9%. (3) response to highly motivated students to cooperative learning Take and Give the percentage is 95%. Based on these studies it can be concluded that the application of cooperative learning model of Take and Give can improve student learning outcomes in the discussion Petroleum class X-2 MAN Sabang